``American with a Czech Heart''. Forman about Forman also from Different Perspectives - Pradna, Stanislava (Iluminace, 2008)
A portrait of Milos Forman, in which the author focuses on the connections between his work and his personal story from the perspective of Forman's autobiography What Do I Know? or What Should I Do If It's True?
Keywords: Czech directors; emigrants; screenwriters; Czech New Wave; memoirs